Contribuições para a ciência brasileira: Marcelo Damy de Souza Santos - Silva, Valdir Carlos da (2006)
We present on the work, a soon Physics's history during the century XIX and the three first decade of century XX. We relate the principal Physics's Happenings on this time and her influence in the arising of first Brazilian Physicols and the first Phisycs reserches between 1920 and 1950 at the Brazilian Universities. We treat with reverence here the Phisicol Teacher Marcello Damy de Souza Santos, for his contribution to Phisics Science at Brazil, essentialy on Second World War with the construction of the Sonar for the Brazilian Naval Force. The internatinal recognition that he provided to the Brazil and the Brazilian Universities, investments in equipments and researchs